Measuring Conceptual Associations via the Development of the Chinese Visual Remote Associates Test - Wu, Ching-Lin; Chen, Pei-Zhen; Chen, Hsueh-Chih (Frontiers in Psychology, 2022)
Multiple versions of the Chinese Remote Associates Test (CRAT) have been developed. Thus far, all CRATs have employed verbal stimuli; other forms of stimuli have not yet been used. In this context, the present study compiled a Chinese Visual Remote Associates Test (CVRAT) that conforms to the Chinese language and culture based on a picture naming database. The developed CVRAT has two versions, CVRAT-A and CVRAT-B, each comprising 20 test questions. A typical CVRAT question consists of three stimuli pictures, requiring respondents to propose a target word that is semantically associated with all the pictures. When compiling the CVRAT, this study first selected target words, sifted through stimuli words and corresponding pictures, and analyzed pilot test questions. After compilation, their reliability and validity were examined. The results showed that the CVRAT had moderate internal consistency reliability, good criterion-related validity for the Chinese Word Remote Associates Test (CWRAT), Chinese Radical Remote Associates Test (CRRAT), Chinese Compound Remote Associates Test (CCRAT), insight problem-solving, as well as acceptable discriminant validity for fluency, flexibility, and originality of a divergent thinking test. In other words, CVRAT can effectively measure remote associative capability and provides a figural creativity test that facilitates the understanding of different kinds of remote associations.